Akuntabilitas Penatausahaan, Pelaporan Dan Pertanggungjawaban Dana Desa - Sri Ayu Saputri; Nurzi Sebrina; Vita Fitria Sari (Universitas Negeri Padang, 2019)
This study aims to determine how Administration, Reporting and Accountability of Dana Nagari in Batang Anai District, Padang Pariaman Regency, West Sumatra Province. There are three (3) aspects in village funds, administration, reporting and accountability. To achieve these objectives, descriptive qualitative research methods are used. Data sources are primary data and secondary data. Data collection techniques are carried out by observation, interviews, and documentation using qualitative descriptive analysis techniques. The results of the study show: (1) Administration carried out by the treasurer in the form of receipts and expenditures which are recorded in the general cash book, bank book, income details book, and financing details book which is equipped with receipts. (2) Reporting that the delay in disbursing village funds was due to the late regulation of the Regulations of the Regent of Padang Pariaman which caused the disbursement of stage I and phase II village funds to be delayed too late. (3) Accountability Submission of accountability reports to the public through various media, such as websites and billboards. Submission through this media can make it easier for the public to obtain information about the performance of the village government.